Sexual citizenship : the material construction of sexualities - Evans, David T. (David Trevor), 1945- (Routledge, 1993)
Argues that analyses of social construction of sexualities have ignored the material contexts in which gender construction occurs. Evans maintains that the progressive sexualization of modern capitalist societies is shaped by the complex inter-related material interests of market and state.